2021
DOI: 10.1097/mca.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Early coronary healing in ST segment elevation myocardial infarction: sirolimus-eluting stents vs. drug-coated balloons after bare-metal stents. The PEBSI-2 optical coherence tomography randomized study

Abstract: Objectives Drug-coated balloons (DCBs) have theoretical advantages over drug-eluting stents (DESs) to facilitate stent healing. We studied whether, in patients undergoing primary coronary interventions (pPCIs), a strategy of DCB after bare-metal stent improves early healing as determined by optical coherence tomography (OCT) compared with new-generation DES. Methods pPCI patients were randomized (1:1) to treatment with new-generation sirolimus-eluting stents (DES group) or DCB-strategy. Vessel healing was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The newer generation of DES which were implanted with biocompatible polymers or biodegradable polymers, enabling an extremely low in ammatory response and thrombogenicity, resulting in faster, integrity and well-functioning endothelial restoration (21). DCB is playing an increasingly important role in PCI with advanced and optimal endothelial healing (22). Fast healing of the endothelium leads to reduction in the strength of antiplatelet therapy and thus reduces the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The newer generation of DES which were implanted with biocompatible polymers or biodegradable polymers, enabling an extremely low in ammatory response and thrombogenicity, resulting in faster, integrity and well-functioning endothelial restoration (21). DCB is playing an increasingly important role in PCI with advanced and optimal endothelial healing (22). Fast healing of the endothelium leads to reduction in the strength of antiplatelet therapy and thus reduces the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The study used minimal lumen area to compare the two devices. The PEBSI-2 OCT study [24] used OCT to evaluate the healing patterns after 90 days in patients undergoing primary PCI with either the O-SES or implantation of a bare-metal stent followed by drug-coated balloon dilatation. Similar low rates of malapposed (2%) and uncovered struts (3%) were found in the two groups.…”
Section: Vascular Healing Indexmentioning
confidence: 99%
“…The PEBSI Study (DCB-combined therapy) revealed the beneficial impacts of PCB angioplasty with BMS for the reperfusion therapy of STEMI, particularly with regards to early ( 3 ) and late coronary healing, at the affected site of STEMI. Optical coherence tomography (OCT) revealed a low rate of uncovered struts (3.2%), a high rate of covered and apposed struts (96.1%), and, compared to BMS-alone therapy, showed significant reductions of major coronary evaginations (approximately 42.2%), as well as a significantly higher rate of development of thin homogeneous neointimal layer (approximately 3.5 times), after only a brief but effective application of paclitaxel after BMS implantation ( 3 ). Therefore, additional PCB angioplasty is likely to reduce the probability of the mal-apposition of BMS, with the drug (paclitaxel) facilitating acute coronary healing by suppressing evagination on the BMS.…”
mentioning
confidence: 99%
“…At present, both of the DCB-combined therapies ( 1 , 4 ) cannot be applied in clinical settings due to the fact that BMS have been unavailable. In addition, all of the frequencies of the OCT-detected parameters of the PEBSI Study ( 3 ) have been significantly improved in more recent DES ( 6 ). Consequently, adverse late coronary healing due to MACE have significantly reduced due to the use of recent DES.…”
mentioning
confidence: 99%